Problem Solving Methods for Design Ideation: Building Creativity in Interior Design Projects. (Al-Academy, 2024)
Interior design students face challenges in understanding creativity and applying it while designing. Many techniques and methods are taught to students to encourage the creative design ideation process. One of the most effective techniques that aid in creativity is the Creative Problem-Solving technique. This research aims to investigate and analyze the creative problem-solving method, and its relation to creativity. Specifically, it investigates how well do interior design students understand creativity and how to apply the creative problem-solving method correctly. In this context, creative problem-solving method is defined as a process in which designers create new problems for their projects, to be able to find new solutions for them. To gain a deeper insight about creativity and the creative problem-solving technique from the students’ perspective, an online survey was distributed, and an interview was conducted. The online survey was distributed to interior design students at different educational levels, and across the world. While the survey was conducted with a bachelor interior design student from University of Sharjah. The results aroused some unexpected questions and conclusions. The results showed that although students are confident of their creativity and aware about the creative problem-solving technique, they are still not applying it correctly and effectively.